Peningkatan Kemampuan Membaca Al-Qur’an Melalui Program Klinik Al Qur’an di SMK Negeri 15 Jakarta - Arti Yulyani; Shobah Shofariyani Iryanti (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The life of every Muslim cannot be separated from the Qur'an, because it is a guide and guide to life. However, in reality, many of the current generation still do not understand the basics of reading the Qur'an. The purpose of this research is to determine the efforts of PAI teachers to improve the ability to read the Al Qur'an of students at SMK Negeri 15 Jakarta. The subjects of this research were PAI teachers at SMK Negeri 15 Jakarta. The object of this research is the program "Al Qur'an Clinic in improving the ability to read the Qur'an at SMK Negeri 15 Jakarta”. Data collection techniques were carried out by means of interviews, observation and documentation. Data was analyzed using qualitative descriptive. The results of the research concluded that the Al Qur'an clinic program carried out by PAI teachers provides motivation to students to increase their interest in reading the Al Qur'an and creates comfortable learning in direct Al Qur'an Clinic activities, providing explanations and understanding to students how important it is to read and memorize, especially for life in this world and the hereafter.